P1331OPTIMAL PLANNING OF VASCULAR ACCESS IS CALLED FOR IN WOMEN. AVF ARE MORE INTERVENED AND ABANDONED DESPITE LESS CO-MORBIDITY. (6th June 2020) - Welander, Gunilla; Lundin, Fredrik; Sigvant, Birgitta
Abstract: Background and Aims: Central venous catheter (CVC) increase the risk of infection, central stenosis, hospitalizations, morbidity, mortality and later arterio-venous (AV) access failure. Vascular access planning begins in the predialysis stage of Chronic Kidney Disease (CKD). An optimal timely referral to vascular surgeon is possible since 80 % of patients are known to kidney units before initiating hemodialysis (HD). Despite this, some 71 % (75% women and 68 % men respectively) of incident patients had a CVC as vascular access when starting HD in Sweden during 2017. Some reports have shown increased risk of AVF failure in women which has been contradicted by others. The aim of this study was to determine factors of importance for achieving a functioning fistula for women and men. Method: Data from the national Swedish Renal Registry (SRR), that covers the disease progression from CKD phase to renal replacement therapy, was used as well as mandatory national registries. Data was extracted from 2011 to 2017 for, sex, age, primary renal diagnosis, number of CVC, patient phase, co-morbidity, socio-economic factors as well as interventions and complications. A Royston-Palmer model was used for hazard ratio (HR). Cumulative incidence plots were used for fistula patency. P value < .005 was considered significant Results: The study included 5040 patients at baseline (33% women). The mean age, the time in dialysis before fistula placement and numbers of CVC did not differ between the sexes. Prevalence of polycystic kidney disease was the only primary diagnosis that differed between the sexes (10.7% among women versus 6.5% among men respectively p<.01). Cancer, hypertension and ischemic heart disease, was more prevalent among men (24.0 vs 19.1 p<.001, 80, 9% vs 75.7, p<.001 and 25.3 vs 18.0 p<001). Education level were similar between the sexes whereas more men were married and born in Sweden as compared women (49.3 vs 41.6 p<.001 and 78.9 vs 73.0 p<.001). Age, diabetes and peripheral arterial disease increased the risk for reinterventions by 6% and 28% and 36% (HR 1.06 [1.03, 1.15], 1.28[1.18, 1.40], and 1.36[1.19, 1.56] respectively. The risk for reintervention and abandonment was higher for women (HR 1.19 [95% CI: 1, 09, 1, 56, and 1.42[1, 26, 1.60)]. Figure 1 . shows cumulative incidence for primary patency in lower arm fistula for men and women. Incidence of secondary patency abandonment is higher for women with lower and upper arm AVF while no differences between men and women were observed for AV grafts. Conclusion: When receiving the first fistulas, men present a higher co-morbidity as compared to women while age and time of dialysis with a CVC is similar between the sexes. Only 42% will receive an AVF in CKD phase with detriment for men. The consequence of placement in CKD phase could matter and needs to be further analysed. AVF confers a higher risk for reintervention and abandonment, particularly among women which may explain the higher use of CVC. This higher risk must be taken into account when planning for vascular access and follow up.